Hate Speech on Social Media: the Urgency of Criminal Law Regulation and Approaches - Samuji (Universitas Muhammadiyah Palu, 2024)
The spread of hate speech on social media is one of the results of rapid advances in information and communication technology. However, these advancements have also created new opportunities for social interaction. Hoaxes that appear on the internet often have negative social, psychological, and even political consequences. This study aims to determine the importance of regulating hate speech in social media and analyze methods that can be used in criminal law to deal with the spread of hate speech. Using the descriptive analysis method, this study shows that the current regulations are weak and ineffective, so a firmer method in criminal law is needed to deal with the spread of hate speech. The study also emphasizes how important it is to work together between governments, social media platforms, and the public to prevent hate speech from spreading.